The foundations of defiance: examining the psychological underpinnings of ethnic minority defiance toward police - Sargeant, Elise (Policing and society, 2023)
Defiance can be a powerful mechanism of protest against police oppression. At the same time, citizen defiance to police authority is problematic for police and can cause injury to both police officers and the public. Research shows that some groups of people defy police more than others, and that defiance often represents a reaction to disenfranchisement, police bias and unfair treatment. For example, the Black Lives Matter movement has highlighted that Black, First Nations peoples and racial/ethnic minority groups are more likely to experience problematic relationships with the police. This study focuses on understanding the factors that drive defiance toward police within two ethnic minority communities in Australia. Testing a new theoretical model, we find that procedural injustice from police can create identity threats, thus explaining why some ethnic minority individuals choose to defy the police. Alternatively, procedural justice may reduce identity threats and defiance.